Discovery of functional PRRs for the fungal elicitor Xyn11/eix in Prunus fruit trees - Andree Alvarez; Uri Aceituno-Valenzuela; Meirav Leibman-Markus; Daniela Muñoz; Carlos Rubilar; Franco Figueroa; Manuel Pinto; Mauricio Latorre; Claudia Stange; Adi Avni; Maya Bar; Lorena Pizarro (Plant Stress)
Pattern-triggered immunity (PTI) is a critical defense mechanism employed by plants against pathogen attacks. This study explores the role of PTI induced by the Xyn11/eix fungal elicitor in two commercially valuable Rosaceae species, Prunus persica (peach) and Prunus avium (sweet cherry). Our findings demonstrate that Xyn11/eix triggers two specific defense responses: the increase in ethylene production and the induction of cell death. Furthermore, Xyn11/eix-mediated PTI significantly reduces the susceptibility to Botrytis cinerea infection in both species. The study reveals changes in gene expression patterns after Xyn11/eix treatment. Notably, ACO1 and SARDEF1 genes, involved in ethylene and salycilic acid biosynthesis, respectively, are upregulated in P. persica, but not in P. avium at the time point analyzed. This result suggests a potential role for the ethylene and salicylic acid signaling in Xyn11/mix-mediated PTI in P. persica. Additionally, the research identified functional orthologues of LeEIX2, the receptor for Xyn11/eix in Solanum lycopersicum, within both Prunes genomes. Altogether, these results suggest a remarkable functional convergence between Rosaceae and Solanaceae plants in the Xyn11/eix mediated defense responses although not at the transcriptional level, and opens new avenues for developing novel disease control strategies for stone fruits.